Petrology, zircon U-Pb geochronology and tectonic implications of the A1-type intrusions: Keban region, eastern Turkey - Erturk, Mehmet Ali; Sar, Abdullah; Rizeli, Mustafa Eren (Elsevier Gmbh, 2022)
The Southeast Anatolian Orogenic Belt (SAOB), the most extensive segment of the Alpine-Himalayan Orogenic Belt, resulted from the northward subduction of the southern branch of the Neotethys oceanic crust beneath the Anatolian micro-plate. We present new whole-rock geochemistry, zircon U-Pb ages, and Lu-Hf isotope data from the stocks and dykes with a length of up to tens of meters belonging to the Keban magmatic rocks, eastern Turkey. These rocks are represented by syenite and quartz monzonite intruded into the Keban metamorphic complex. The geochemistry data indicates that the samples bear mostly metaluminous, variably high alkalines (K2O + Na2O), Ga/Al ratios and zircon saturation temperature, and typically the A-type granite characters. According to the Y/Nb vs Yb/Ta diagram, the Keban magmatic rocks show A1-type geochemical signatures modified by crustal melts. Syenite and quartz monzonite samples from Keban magmatic rocks give zircon U-Pb ages of 77.4 +/- 0.34 Ma, 76.3 +/- 0.3 Ma and 76.36 +/- 0.34 Ma, respectively. On the primitive mantle-normalised trace element patterns, the Keban magmatic rocks show enrichment in large-ion lithophile elements (LILEs) relative to high field strength elements (HFSEs). They are coupled with slightly negative Nb-Ta anomalies. Chondrite-normalised rare earth-element patterns show strong enrichment in LREEs relative to HREEs, a typical A-type granites feature. The zircons have negative epsilon Hf(t) values that vary from-2.68 to-0.41, and Hf model ages (TDM2) range from 1171.54 to 1329.26 Ma, indicating the enriched lithospheric mantle sources and crustal contribution. The sources and evolution of the alkaline magmas might be related to the post-collisional tectonic setting.
Keywords: A 1-type granitoid; Keban magmatic rocks; Petrology; Zircon U-Pb chronology; Lu-Hf isotope; Eastern Turkey